2020
DOI: 10.1002/ehf2.13031
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopoietic stem cell therapy in ischaemic heart failure: long‐term clinical outcomes

Abstract: Aims This study aims to explore long-term clinical outcomes of cardiopoiesis-guided stem cell therapy for ischaemic heart failure assessed in the Congestive Heart Failure Cardiopoietic Regenerative Therapy (CHART-1) trial. Methods and results CHART-1 is a multinational, randomized, and double-blind trial conducted in 39 centres in heart failure patients (n = 315) on standard-of-care therapy. The 'active' group received cardiopoietic stem cells delivered intramyocardially using a retention-enhanced catheter. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Moreover, injection of bone marrow mesenchymal cells with or without c-kit positive cardiac cells improved the patients' quality of life compared to placebo ( 36 ). In the CHART-1 trial, intramyocardially injected cardiopoietic stem cells were associated with reduced risk of death or cardiovascular hospitalization in a subpopulation of patients with advanced LV enlargement as compared to a sham procedure ( 37 ). Despite the lack of evidence in reduction of infarct scar area or improvement in LVEF, these encouraging results indicate that cell-based therapies can have long term effects in preventing progression of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, injection of bone marrow mesenchymal cells with or without c-kit positive cardiac cells improved the patients' quality of life compared to placebo ( 36 ). In the CHART-1 trial, intramyocardially injected cardiopoietic stem cells were associated with reduced risk of death or cardiovascular hospitalization in a subpopulation of patients with advanced LV enlargement as compared to a sham procedure ( 37 ). Despite the lack of evidence in reduction of infarct scar area or improvement in LVEF, these encouraging results indicate that cell-based therapies can have long term effects in preventing progression of HF.…”
Section: Discussionmentioning
confidence: 99%
“…136 Up to date, stem cells with different origins (embryonic, fetal, and adult tissues) and differentiation potency (e.g., pluripotent and multipotent) were utilized for improving neo-vessel formation and consequently enhanced functional recovery of the ischemic heart. 137 Regarding the literature, initial reports indicated that adult stem cells (e.g., MSCs) could enhance neo-vessel formation through differentiation toward ECs lineages. Over time, some faulty published studies led to serious concerns about adult stem cell differentiation toward ECs and their putative roles in promoting angiogenesis.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…Conventionally, selection of candidates for cardiac stem cell therapy relies on a cut-off value, such as LV ejection fraction <40%. Recent clinical study sub-analyses, however, document signs of cardiopoietic stem cell efficacy associated with a tight phenotypic profile, namely a range of LV dilatation, a marker of organ remodeling [ 46 , 47 ]. Candidate titration was validated in a model of staged infarction size.…”
Section: Pretherapy Stratificationmentioning
confidence: 99%